Attributable causes of chronic kidney disease in adults: a five-year retrospective study in a tertiary-care hospital in the northeast of the Malaysian Peninsula - Salman, Muhammad; Hayat Khan, Amer; Adnan, Azreen Syazril; Syed Sulaiman, Syed Azhar; Hussain, Khalid; Shehzadi, Naureen; Jummaat, Fauziah (Associação Paulista de Medicina, 2015)
CONTEXT AND OBJECTIVE: Chronic kidney disease (CKD) is an escalating medical and socioeconomic problem worldwide. Information concerning the causes of CKD, which is a prerequisite for reducing the disease burden, is sparse in Malaysia. Therefore, this study aimed to evaluate the attributable causes of CKD in an adult population at a tertiary referral hospital. DESIGN AND SETTING: Retrospective study at Hospital Universiti Sains Malaysia (HUSM). METHODS: This was an analysis based on medical records of adult patients at HUSM. Data regarding demographics, laboratory investigations, attributable causes and CKD stage were gathered. RESULTS: A total of 851 eligible cases were included. The patients’ mean age was 61.18 ± 13.37 years. CKD stage V was found in 333 cases (39.1%) whereas stages IV, IIIb, IIIa, and II were seen in 240 (28.2%), 186 (21.9%), 74 (8.7%) and 18 (2.1%), respectively. The percentage of CKD stage V patients receiving renal replacement therapy was 15.6%. The foremost attributable causes of CKD were diabetic nephropathy (DN) (44.9%), hypertension (HPT) (24.2%) and obstructive uropathy (9.2%). The difference in the prevalence of CKD due to DN, HPT and glomerulonephritis between patients ≤ 50 and > 50 years old was statistically significant. CONCLUSION: Our results suggest that DN and HPT are the major attributable causes of CKD among patients at a Malaysian tertiary-care hospital. Furthermore, the results draw attention to the possibility that greater emphasis on primary prevention of diabetes and hypertension will have a great impact on reduction of hospital admissions due to CKD in Malaysia.